(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Development of an economy necessarily depends upon itsfinancial system and the rate of new capital formation which can be achieved bymobilizing savings and adopting an investment pattern, be its self-financingi.e. direct or indirect where financial intermediaries like banks, insuranceand other financial companies come in the picture and mediate between saversand borrowers of funds. The need to mobilize small savings of household sectorand to channelize it for productive purpose through financial markets, furtherleads to the emergence of mutual funds which help the small investors to pooltheir scattered small savings and to invest in those securities which otherwisewould not have been possible individually. An efficient, articulate and developed financial systemis a must for the rapid economic growth and development of a country. Financialsystem facilitates the transformation of savings of individuals, governmentsand businesses into investment and consumption. A complete system is formed ofspecialized and non-specialized intermediaries, organized and non-organizedfinancial markets and financial instruments and services. Financialinstitutions act as a mobilisors and depositories of savings, purveyors ofcredit and also providers of various financial services to the community. Thefinancial system helps accelerate the rate of economic development and therebyimprove the standard of living and increase the social welfare of the community.This is achieved by the financial system through mobilizing the savings andinvesting them gainfully.